Challenges in the Dental Management of Rett Syndrome under General Anesthesia: A Rare Disease - Wisam Al-Hathlol; Raed Bokhari; Nada Alzahrani; Elaf Alkuwaiti (Case Reports in Dentistry)
Rett syndrome is a neurodevelopmental genetic X-linked disorder. It is predominantly found in females with a prevalence rate of 1 : 9000. Rett syndrome patients are usually healthy the first months of their lives. The syndrome goes into a deceleration phase where motor, behavioral, and cognitive skills are impaired. Regarding their oral health, bruxism is one of the common oral manifestations found among Rett syndrome patients. We present a case of an 8-year-old patient with Rett syndrome who presented to the dental clinic for oral rehabilitation. The patient was evaluated and treated under general anesthesia with multiple extractions, restorations, and crown installments. Oral rehabilitation of Rett syndrome is important for those patients, and proper evaluation and treatment are the most efficient when performed under general anesthesia.